Ultrasonographic and resistance index evaluation of nails in psoriatic arthritis, psoriasis, and control groups : a cross-sectional study - Rossi, Samanta Daiana de (2021)
Background: Nail psoriasis occurs frequently in patients with psoriatic disease, it can lead to functional impairment, pain, discomfort, decreased quality of life and can also be a predictor for the development of arthritis. Early recognition of this condition can provide early and effective treatment and prevent structural impairment. This study aims to identify nail ultrasonographic characteristics in three groups: psoriasis (PsO), psoriatic arthritis (PsA) and controls patients, to determine if the ultrasonography (US) can identify early signs of nail psoriatic impairment or local inflammation. We conducted nail US to determine nail matrix resistance index (NMRI), nail bed resistance index (NBRI), and power Doppler (PD) and grayscale (GS) parameters in these 3 groups. Methods: Single-center, cross-sectional study. GS, PD, and spectral doppler images of bilateral 2nd and 3rd fingernails were acquired from 35 PsO, 31 PsA, and 35 controls patients. An US equipment with an 18 MHz linear transducer for GS and 8.0 MHz for PD was used. PD, NMRI, NBRI, nail plate thickness (NPT), nail bed thickness (NBT), nail matrix thickness (NMT), and morphostructural characteristics of the trilaminar structure (TS) were evaluated in saved images, blind. Results: Mean NMRI and NBRI did not differ between groups. Linear regression analysis detected no relationships between PsO or PsA and NMRI or NBRI. Nail PD grade did not differ between groups. Type I and IV TS changes were more frequent in PsO; types II and III changes were more frequent in PsA (p < 0.001). NPT was greater in PsA and PsO groups than controls: PsA 0.73 ± 0.14 mm, PsO 0.72 ± 0.15 mm, Controls 0.67 ± 0.10 mm (p = 0.001). Conclusion: Echographic TS characteristics of the nail plate and NPT evaluated by GS are useful and can distinguish PsO and PsA nails from controls. NMRI, NBRI, and US nail microcirculation parameters could not distinguish psoriatic nails.